THE RELATIONSHIP MODEL OF CREATIVE ECONOMY CONCEPTS THAT AFFECT MARKETING SUCCESS - Chummee, Pattarapon (International Journal of Research -GRANTHAALAYAH, 2023)
The objectives of this research article are 1) to study the general characteristics of community enterprise entrepreneurs and 2) to analyze the influence between creative economy concepts on marketing success. This research is quantitative research. Data were collected from 310 community enterprise entrepreneurs in Bangkok and its vicinity. The research tools were questionnaires that tested the concordance values between 0.60-1.00. The statistics used in the research consisted of descriptive statistics, factor analysis and path analysis. The results showed that most of the respondents were male, 178 people, representing 59 percent. The number of employees found that the largest number was between 21-40 with a total of 242 people. In the term of education, the result found that the large number of respondents graduate with bachelor's degree was 250 people, representing 83.3 percent. The result of age showed that the sample group was between 51-60 years old was the largest number of 240 people, representing 80 percent. And the results of influence path analysis revealed that creative economy concept variables to marketing success found that the coefficient was 0.579. For the marketing success to the competitive advantage had a path coefficient at 0.008 and the correlation path between marketing success to competitive advantage had a path coefficient of 0.0995.